2019
DOI: 10.1016/j.jgar.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter in veterinary medicine, with an emphasis on Acinetobacter baumannii

Abstract: Acinetobacter spp. are aerobic, rod-shaped Gram-negative bacteria belonging to the Moraxellaceae family of the class Gammaproteobacteria and are considered ubiquitous organisms. Among them, Acinetobacter baumannii is the most clinically significant species with an extraordinary ability to accumulate antimicrobial resistance and survive in the hospital environment. Recent reports indicate that A. baumannii has also evolved into a veterinary nosocomial pathogen. Although Acinetobacter spp. can be identified to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 140 publications
0
56
0
1
Order By: Relevance
“…This however, does not apply to veterinary medicine. The current knowledge on antibiotic resistance in A. baumannii from animal origin is mostly based on internationally published case reports, investigations of strain collections and several whole genome analyses as summarised by Müller et al (2014) and van der Kolk et al (2018). This lack of data results in a somewhat sketchy picture on how to assess the impact of drug resistant A. baumannii strains on veterinary and public health.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This however, does not apply to veterinary medicine. The current knowledge on antibiotic resistance in A. baumannii from animal origin is mostly based on internationally published case reports, investigations of strain collections and several whole genome analyses as summarised by Müller et al (2014) and van der Kolk et al (2018). This lack of data results in a somewhat sketchy picture on how to assess the impact of drug resistant A. baumannii strains on veterinary and public health.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of data results in a somewhat sketchy picture on how to assess the impact of drug resistant A. baumannii strains on veterinary and public health. It is not yet clear if animals indeed pose a risk as reservoir for A. baumannii; genetically distinct animal isolates have been reported by Wilharm et al (2018) and by van der Kolk et al (2018), whereas companion animals have been found to carry isolates more closely related to human strains (Ewers et al 2017;Walther et al 2018), which could be an indication for humans possibly infecting their pets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations